Efficient Na‐Ion Storage in 2D TiS2 Formed by a Vapor Phase Anion‐Exchange Process. Issue 10 (2nd September 2020) - Zhuo, Sifei; Huang, Gang; Lei, Yongjiu; Wang, Wenxi; Liu, Zhixiong; Xu, Xiangming; Yin, Jian; Alshareef, Husam N
Abstract: Hierarchical nanocomposites that couple downsized 2D materials with carbonaceous functional supports are promising electrode materials for metal ion batteries. Herein, a honeycomb‐like Na‐ion battery (NIB) anode material, which comprises 2D downsized TiS2 nanocrystals uniformly dispersed in a 3D porous carbon honeycomb, is developed by a vapor phase anion‐exchange reaction of CS2 with a dual‐template of TiO2 sealing in hydrogen‐substituted graphdiyne (HsGDY). On the one hand, the 2D downsized TiS2 nanolayers offer much more accessible active sites for both Na + storage and polysulfide trapping; on the other hand, the 3D porous hollow carbon nanoscale honeycomb not only provides numerous space‐confined nanorooms to reduce the stacking of the tiny 2D TiS2 nanolayers and suppress the dissolution of polysulfide, but also works as built‐in 3D conductive networks to support the electron/ion transfer and buffer the volume expansion during cycling. In light of this, such a hybrid 3D TiS2 @carbon honeycomb achieves a high reversible capacity with high‐rate and long‐life performance for NIBs. Abstract : To improve the capacity utilization of 2D materials, a space‐confined dual‐templating method is demonstrated for downsizing TiS2 into tiny nanolayers in a 3D porous carbon honeycomb. Such a hybrid nano‐assembly combines both physical stability and conductivity of carbon and chemical reactivity of TiS2 in one system, resulting in a high‐rate and long‐life anode material for Na‐ion batteries.